Pengaruh CAR, NPL dan LDR Terhadap Profitabilitas pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2008-2011 - Satriawan, Gede Hendra Yudha; Sudiartha, Gede Mertha (E-Jurnal Manajemen, 2013)
This study aimed to analyze the effect of capital adequacy ratio, non performing loans and loan t o deposit ratio on profitability in banking companies listed on the Indonesian stock exchange. This study determined the sample through purposive sampling method that can be obtained 11 samples of 30 banking companies in the observation period 2008-2011. Methods of testing performed in this study using multiple linear analysis. The results of this study indicate that the capital adequacy ratio, non performing loans and loan to deposit ratio simultaneously significant effect on profitability. Partially capital adequacy ratio and no significant negative effect on profitability, non performing loans and a significant negative effect on profitability and loan to deposit ratio and no significant positive effect on profitability. Keywords: Profitability, Capital Adequacy Ratio, Non Performing Loan, Loan To Deposit Ratio